2015
DOI: 10.14411/fp.2015.066
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anti-Toxoplasma gondii antibodies in stutterers is higher than in the control group

Abstract: The purpose of this study was to investigate the possible relationship between Toxoplasma gondii (Nicolle et Manceaux, 1908) and stuttering. We investigated the seropositivity rate for anti-T. gondii IgG and antibodies by enzyme-linked immunosorbent assay (ELISA) in stuttering children to ascertain a possible relationship between T. gondii infection and stuttering. We selected 65 stuttering children and 65 control children (non-stutterers) to investigate the seropositivity rate of anti-T. gondii antibodies by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…All these processes also occur during toxoplasma infection [17]. Furthermore, there is evidence that infection with T. gondii has a greater impact on the hippocampus and amygdala [15]. A relationship has been observed with the synthesis of neurotransmitters such as dopamine and serotonin, also related to the other pathologies cited in this work (dopamine in Tourette, autism, hyperactivity, and serotonin in depression), combined impairment of dopaminergic regulation and presynaptic serotonergic with dopaminergic transmission dysfunction [17,19].…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…All these processes also occur during toxoplasma infection [17]. Furthermore, there is evidence that infection with T. gondii has a greater impact on the hippocampus and amygdala [15]. A relationship has been observed with the synthesis of neurotransmitters such as dopamine and serotonin, also related to the other pathologies cited in this work (dopamine in Tourette, autism, hyperactivity, and serotonin in depression), combined impairment of dopaminergic regulation and presynaptic serotonergic with dopaminergic transmission dysfunction [17,19].…”
mentioning
confidence: 60%
“…Only a study showed a significant association between hyperactivity disorder and gender, being more prevalent in men [19]. No significant differences related to area of residence [15] or socioeconomic status [13,18] were identified. However, significant differences were found in the assessments of the scales measuring the severity of Tourette [16], autism [17], hyperactivity [19], and anxiety and OCD [14], observing more severe symptoms in seropositive patients.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations